2022
DOI: 10.3390/v14061169
|View full text |Cite
|
Sign up to set email alerts
|

Low Susceptibility of Rubella Virus in First-Trimester Trophoblast Cell Lines

Abstract: We recently published an article about myelin oligodendrocyte glycoprotein-independent rubella infection of keratinocytes in vitro, in which first-trimester trophoblast cells were shown as rubella virus (RuV)-resistant. Given an incident rate as high as 90% of congenital rubella syndrome in the first eight weeks of pregnancy, the RuV infection of first-trimester trophoblasts is considered key to opening the gate to transplacental transmission mechanisms. Therefore, with this study, we aimed to verify the susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Current articles have reported that trophoblast cells are resistant to many viral infections, including RuV (Bayer et al, 2015;Trinh et al, 2018). Our latest experimental results showed that RuV has low infectivity to the first-trimester trophoblast cell lines HTR-8/SVneo and Swan.71 in vitro (Pham et al, 2022). Early studies suggested that transplacental RuV infection targets fetal endothelial cells and Hofbauer cells instead of trophoblasts (Perelygina et al, 2013(Perelygina et al, , 2015.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Current articles have reported that trophoblast cells are resistant to many viral infections, including RuV (Bayer et al, 2015;Trinh et al, 2018). Our latest experimental results showed that RuV has low infectivity to the first-trimester trophoblast cell lines HTR-8/SVneo and Swan.71 in vitro (Pham et al, 2022). Early studies suggested that transplacental RuV infection targets fetal endothelial cells and Hofbauer cells instead of trophoblasts (Perelygina et al, 2013(Perelygina et al, , 2015.…”
Section: Discussionmentioning
confidence: 90%
“…We recently discovered that RuV has low infectivity to the first-trimester trophoblast cell lines HTR-8/SVneo and Swan.71 in vitro, suggesting that there might be other factors affecting the infectivity of RuV to these cells (Pham et al, 2022). Searching for such possible factors led us to hypothesize that ER stress may play a role in RuV infection in early pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…The reports on the susceptibility of trophoblast cell lines to RuV are divergent. A low susceptibility on first-trimester HTR-8/SVneo and Swan.71 [14] opposes susceptibility analysis of choriocarcinoma cell lines JAR and JEG3 to VSV pseudotyped with RuV structural proteins and a recombinant RuV in a CRISPR/Cas9 genome-wide knockout screening [15,16]. Thus, we aimed at RuV infection mechanisms and antiviral response mechanisms in human choriocarcinoma BeWo cell line.…”
Section: Productive Ruv Infection On Bewo After An Initially Low Infe...mentioning
confidence: 99%
“…It is well established that for most of the CRS cases, the infection and vertical transmission occurred in the first trimester [ 9 ]. However, in vitro studies showed that RuV has low infectivity in trophoblasts and suggest that some factors may affect the infection in the first trimester [ 8 , 13 , 92 , 117 ].…”
Section: Viral Infections In Pregnancymentioning
confidence: 99%
“…However, the mechanisms for which these viral infections affect trophoblasts, a natural barrier to prevent the fetus from being infected due to a virally infected mother, are not well understood. Trophoblasts are generally well-known for their resistance or low susceptibility to various viruses [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%